Four centuries of transcultural care - Rosa María Rodríguez Perales; Juan Manuel Arribas Marín; José Carlos Gantes Soto (Universidad de Alicante, 2012)
Founded in the XVIth century, since 1608 the Hospitalary Order of Saint John of God has spread its work to different countries with the aim of caring for patients without distinguishing race, nation, religion or disease. At the present time, it looks after people from different cultures with a particular style established by the founder of the institution. In this article we analyze the principles that determine its own institutional culture: humanization, hospitality, solidarity, love, charity, justice, liberty, dignity, communication and listening. All of them are basic for working within cultural diversity and essential for the development of transcultural care and for the practice of modern nursing. Nursing from a Saint John of God perspective implies a humanistic and transcultural care based on the welfare of people providing a great stream of solidarity that will allow a change of attitudes and of the present unfair establishment.